Biphasic biomimetic scaffolds based on a regionally decalcified bone framework and pre-chondrogenic microspheres for osteochondral defect repair - Zhuo Liang; Qingqing Pan; Fei Xue; Jingdi Zhang; Zhenlin Fan; Weiyun Wang; Xueqiang Guo; Zhuang Qian; Yaping Shen; Wenjuan Song; Lei Wang; Guangdong Zhou; et al. (Materials Today Bio)
Osteochondral defects are still facing a significant challenge in clinical surgery, making post-trauma repair difficult. Tissue engineering has provided a promising approach to solving these defects. However, existing scaffolds cannot replicate the complex biphasic cartilage-bone microenvironment with accuracy. We aimed to develop a biphasic biomimetic scaffold with regionally regulated vascularization that promoted chondrogenesis and osteogenesis through bidirectional regulation of endochondral ossification. This scaffold consisted of pre-chondrogenic microspheres (PCMs) and a decalcified bone frame prepared by decalcifying the cartilage layer and bone layer of the scaffold to varying degrees. Incorporation of PCMs into the cartilage layer created a microenvironment that promoted cartilage regeneration while axitinib was modified to inhibit vascularization and enhance cartilage regeneration. The bone layer provided a microenvironment that promoted endochondral ossification and facilitated bone repair. In vitro studies have shown that axitinib-modified cartilage layers significantly inhibit the VEGF expression of pre-chondrogenic cells, while decalcified bone powder from the bone layer significantly promotes the ossification of PCMs. In vivo experiments indicated that this decalcified bone frame controls the endochondral ossification of PCMs through regionalized angiogenesis, promoting the integrated regeneration and reconstruction of osteochondral defects in rabbit knee joints. These results suggest that our designed demineralized bone frame can precisely engineer the osteochondral regeneration microenvironment, providing theoretical guidance for the integrated regeneration and repair of anisotropic tissue injuries.